Volume 7: Fluids Engineering 2016
DOI: 10.1115/imece2016-68061
|View full text |Cite
|
Sign up to set email alerts
|

Micro Scale Air Sampling Devices: A Numerical Study

Abstract: Numerical simulation of particle collection in a newly developed microfluidic air sampling device is presented in this study. In the simulations, the air carrying the particles is injected into a liquid column to form a bubble. The bubble then releases from the air inlet following with interface deformations and rises in the liquid column carrying the particles inside. During this bubbling process, the particles having impact with the bubble interface are collected in the extraction liquid. For the simulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The slit structure was more conducive to PM purification. 44,45 To achieve the PM ultraultra-low emission standard, new technology desperately needs to be developed. In this study, a slit bubbling structure is developed and designed to purify the PM in a coal-fired flue gas WFGDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The slit structure was more conducive to PM purification. 44,45 To achieve the PM ultraultra-low emission standard, new technology desperately needs to be developed. In this study, a slit bubbling structure is developed and designed to purify the PM in a coal-fired flue gas WFGDs.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the structure of the hole tended to generate larger bubbles that had smaller specific surface areas, while the bubbles generated by the slit were smaller and more uniformly distributed than those generated by the hole structure. The slit structure was more conducive to PM purification. , …”
Section: Introductionmentioning
confidence: 99%